Atrial arrhythmias are associated with increased mortality in pulmonary arterial hypertension. (July 2018) - Smith, Benjamin; Genuardi, Michael V.; Koczo, Agnes; Zou, Richard H.; Thoma, Floyd W.; Handen, Adam; Craig, Ethan; Hogan, Caroline M.; Girard, Timothy; Althouse, Andrew D.; Chan, Stephen Y.
Pulmonary arterial hypertension (PAH) is a deadly vascular disease, characterized by increased pulmonary arterial pressures and right heart failure. Considering prior non-US studies of atrial arrhythmias in PAH, this retrospective, regional multi-center US study sought to define more completely the risk factors and impact of paroxysmal and non-paroxysmal forms of atrial fibrillation and flutter (AF/AFL) on mortality in this disease. We identified patients seen between 2010 and 2014 at UPMC (Pittsburgh) hospitals with hemodynamic and clinical criteria for PAH or chronic thromboembolic pulmonary hypertension (CTEPH) and determined those meeting electrocardiographic criteria for AF/AFL. We used Cox proportional hazards regression with time-varying covariates to analyze the association between AF/AFL occurrence and survival with adjustments for potential cofounders and hemodynamic severity. Of 297 patients with PAH/CTEPH, 79 (26.5%) suffered from AF/AFL at some point. AF/AFL was first identified after PAH diagnosis in 42 (53.2%), identified prior to PAH diagnosis in 27 (34.2%), and had unclear timing in the remainder. AF/AFL patients were older, more often male, had lower left ventricular ejection fractions, and greater left atrial volume indices and right atrial areas than patients without AF/AFL. AF/AFL (whether diagnosed before or after PAH) was associated with a 3.81-fold increase in the hazard of death (95% CI 2.64–5.52, p  < 0.001). This finding was consistent with multivariable adjustment of hemodynamic, cardiac structural, and heart rate indices as well as in sensitivity analyses of patients with paroxysmal versus non-paroxysmal arrhythmias. In these PAH/CTEPH patients, presence of AF/AFL significantly increased mortality risk. Mortality remained elevated in the absence of a high burden of uncontrolled or persistent arrhythmias, thus suggesting additional etiologies beyond rapid heart rate as an explanation. Future studies are warranted to confirm this observation and interrogate whether other therapies beyond rate and rhythm control are necessary to mitigate this risk.